Spreading codes for direct sequence CDMA and wideband CDMA cellularnetworks. - Dinan, E.H (IEEE Communications magazine)
This article presents an overview of the spreading techniques for use in direct sequence CDMA cellular networks. We review the theoretical background for sequences used in CDMA and wideband CDMA, and discuss the main characteristics of the maximal length, Gold (1967, 1968), and Kasami sequences, as well as variable- and fixed-length orthogonal codes. We also describe different methods of multiple spreading for channelization and scrambling in CDMA and W-CDMA realizations